Pengaruh Pupuk Organik Cair Daun Gamal dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Shurt) - Jumiati Jumiati; Adnan Adnan; Lukman Lukman (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2026)
This study aimed to evaluate the interaction and the individual effects of liquid organic fertilizer (LOF) derived from Gliricidia sepium (gamal) leaves and urea fertilizer on the growth and yield of sweet corn (Zea mays saccharata Sturt). The research was conducted from April to June 2025 at the experimental field of Madako Tolitoli University, Tambun Village, Baolan District, Tolitoli Regency. The experiment used a factorial Randomized Block Design with two factors. The first factor was the dosage of gamal leaf LOF consisting of three levels: M0 (without LOF), M1 (200 ml LOF + 800 ml water), and M2 (500 ml LOF + 500 ml water), applied at 100 ml per plant. The second factor was the urea fertilizer dosage: K0 (without urea), K1 (150 kg ha⁻¹ or 3 g per plant), and K2 (300 kg ha⁻¹ or 6 g per plant). There were nine treatment combinations, each replicated three times, resulting in 27 experimental plots measuring 100 cm × 200 cm. Each plot contained 10 plants with a spacing of 40 cm × 50 cm, and five plants per plot were used as samples, giving a total of 135 sample plants. The results indicated that the interaction between LOF and urea significantly affected plant height at 15, 22, 36, and 43 days after planting, as well as leaf number and ear length. Meanwhile, single-factor effects were observed on husked ear weight, ear diameter, number of kernels per row, and dehusked ear weight. The best performance was obtained from the combination of M2K2, namely 500 ml gamal leaf LOF diluted with 500 ml water and 300 kg ha⁻¹ urea, which effectively enhanced both vegetative growth and yield components of sweet corn.